Compatibility of aromatic crops as intercrops in maize (Zea mays L.) in semi-arid region of Karnataka, India - Singh, Munnu (Journal of Spices and Aromatic Crops, 2005)
An experiment was carried out at Bangalore (Karnataka) to investigate the effect of methods of planting (solid row and paired row) and three cropping systems [maize + palmarosa (Cymbopogon martinii), maize + South American marigold (Tagetes minuta) and maize + basil (Ocimum basilicum)] on growth and yield of maize (Zea mays). Grain yield of maize, harvest index and biomass were not affected by intercrop treatments. Land use efficiency in terms of Land Equivalent Ratio ranged between 1.11 to 1.20, the maximum being with maize paired row + palmarosa and maize paired row + South American marigold (20%). There was no effect of method of planting on yield of maize. Palmarosa, South American marigold and basil did not affect the yield of maize. Maximum net returns (Rs. 20,870 ha-1) and benefit : cost ratio (2.26) was obtained with maize paired row + South American marigold.